PENGARUH PENERAPAN CORPORATE GOVERNANCE TERHADAP PENINGKATAN KINERJA KEUANGAN PERUSAHAAN DENGAN FIRM SIZE DAN LEVERAGE SEBAGAI VARIABEL KONTROL (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017 – 2019) - Triana, Tika; Demi Pangestuti, Irene Rini (Faculty of Economics and Business Diponegoro University, 2021)
ABSTRACT The purpose of this research is to analyze the relationship between corporate governance and the firm performance. This research using concentration ownership, institutional ownership, board size, and audit committee as a independent variabel, and then firm performance which is measured by Return on Assets (ROA) as a dependent variabel. In addition, firm size and leverage are used as a control variabel. This research using secondary data and the population of this research is 173 manufactures firms listed on Indonesian Stock Exchange in period 2017 – 2019.By purposive sampling methods, 49 manufactures firms were obtained as the sample of this research. The analytical method used in this research is multiple linear regression analysis. The results of this research indicate that ownership concentration, institusional ownership, and audit committee has a positive and significant effect on firm performance which is measured by ROA, but board size have negative significant effect on firm performance. In addition, based on the results of hypothesis testing, the R square value in this study is 24%, which means that there are still 76% other variabels outside the research variabels used that affect the company's financial performance as measured by return on assets (ROA).